The Effect of Employability and Job Insecurity on Job Satisfaction with Organizational Commitment as a Consequence - Sutanto, Dedy; Kirana, Kusuma Chandra; Subiyanto, Didik (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine the effect of employability and job insecurity on organizational commitment with job satisfaction as a mediating variable. This study focuses on how employability and job insecurity affect organizational commitment, especially in the context of Family Hope Program (PKH) companions in the public sector. A quantitative approach was used in this study by distributing questionnaires to all PKH facilitators in Purworejo Regency totaling 105 people. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, including instrument validity and reliability tests, model fit, hypothesis testing, and mediation analysis. This study provides an empirical contribution by testing the mediation model of job satisfaction in the relationship between employability, job insecurity, and organizational commitment, especially in the local government social sector which has not been widely studied before. The results of the study indicate that employability has a positive and significant effect on organizational commitment, while job insecurity does not have a significant effect on job satisfaction or organizational commitment. Job satisfaction is proven to affect organizational commitment but does not mediate the relationship between employability and job insecurity with organizational commitment. Employability is more decisive for organizational commitment than job satisfaction as an intermediary. Organizational support for increasing employability is key to building organizational commitment.